Pakistan, Sindh Province - Public financial management accountability assessment - World Bank (World Bank, 2012)
This report presents the public financial management and accountability assessment (PFMAA) for Pakistan's Sindh province. The assessment uses the public expenditure and financial accountability (PEFA) 2005 framework, which comprises 31 performance indicators to evaluate: (i) the six core public financial management (PFM) dimensions (credibility of the budget; transparency and comprehensiveness; policy-based budgeting; predictability and control in budget execution; accounting, recording, and reporting; and external scrutiny), and (ii) the extent to which donor practices and the management of donor funds affect the PFM systems in the country. This assessment report highlights the likely impact of PFM weaknesses on budgetary outcomes, aggregate fiscal discipline, the strategic allocation of resources, and efficient service delivery.